Synthesis, Characterization and Analgesic Activity of Cadmium(II) Complex of Tolfenamic Acid: Synthesis, Characterization and Analgesic Activity - Salekin, Sirajis; Sharmin, Tasnuva; Rahman, Md Shahidur (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Tolfenamic acid is a member of fenamate group of non-steroidal anti-inflammatory drugs (NSAID). It is generally used to treat migraine. In recent studies, metal complexes of traditional drugs like, manganese(II) complex of tolfenamic acid and mefenamic acid; cobalt(II) and zinc(II) complexes of tolfenamic acid are reported to give better biological activities than their parent drugs. In this study, tolfenamic acid was complexed with a divalent metal, cadmium(II) to form the drug-metal complex. The peripheral and central analgesic activities of this complex were tested to find out the impact of complexation on the pharmacological activity of the drug. Cadmium nitrate tetrahydrate was used for the complexation reaction and Fourier transform infrared (FT-IR) spectroscopic technique was used to identify the drug-metal complexation. Writhing method and tail flick technique were used to test peripheral and central analgesic activities, respectively in Swiss albino mice model. Comparison of the data obtained for positive and negative controls with the drug metal complex revealed a statistically significant increase in analgesic activities. Extensive experimentation is underway for further development in order to achieve better activity and assess toxicity profiles. Dhaka Univ. J. Pharm. Sci. 19(1): 59-64, 2020 (June)